2010
DOI: 10.1111/j.1399-5618.2009.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between religious involvement and clinical status of patients with bipolar disorder

Abstract: Objective Religion and spirituality are important coping strategies in depression but have been rarely studied within the context of bipolar disorder. The present study assessed the association between different forms of religious involvement and the clinical status of individuals treated for bipolar disorder. Methods A cross-sectional observation study of follow-up data from a large cohort study of patients receiving care for bipolar disorder (n = 334) at an urban Veterans Affairs mental health clinic was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 33 publications
(31 reference statements)
2
24
2
1
Order By: Relevance
“…First of all, their findings may be in line with the hypothesis of Cruz et al (2010) that higher levels of distress as such caused by mixed episodes and/or chronic depression, would prompt patients to seek relief from religion, and therefore increase the frequency of their religious behaviors. However, it could be that, once depressed, HRI patients become the victims of their religious commitment and that, in this case, religion exerts harmful effects on health.…”
Section: Risk Factors Associated With Components Of Religious and Spisupporting
confidence: 65%
“…First of all, their findings may be in line with the hypothesis of Cruz et al (2010) that higher levels of distress as such caused by mixed episodes and/or chronic depression, would prompt patients to seek relief from religion, and therefore increase the frequency of their religious behaviors. However, it could be that, once depressed, HRI patients become the victims of their religious commitment and that, in this case, religion exerts harmful effects on health.…”
Section: Risk Factors Associated With Components Of Religious and Spisupporting
confidence: 65%
“…Furthermore, it has even been suggested that spirituality might reflect little more than a misattribution of pleasant affectivity to stimuli that are undetected by the ‘spiritually unmoved’ (Hicks & King, ; Schuurmans‐Stekhoven). Regardless of cause, the oppositional relationship between affective self‐reports among the spiritual concurs with findings that spirituality is more prevalent among those with bipolar disorder (Cruz et al., ; Galvez, Thommi, & Ghaemi, ; Mitchell & Romans, ) and that those with bipolar disorder tend to attribute their hallucinations to spiritual forces (Hammersley, Taylor, McGovern, & Kinderman, ).…”
Section: Spirituality and Affectivitysupporting
confidence: 75%
“…Depressive and manic states did not correlate with any of the measured dimensions of religiosity. The authors suggested that the greater severity and worse prognosis of mixed states may be reasons for an increase in the frequency of private religiosity behavior as a coping strategy (Cruz et al, 2010). Nonetheless, the way that religiosity and spirituality dimensions change with mood swings is poorly understood (Aubin, 2010).…”
Section: Discussionmentioning
confidence: 98%